Predictive factor of recurrence after endoscopic papillectomy for ampullary neoplasms. (9th June 2021) - Takahashi, Kosuke; Ozawa, Eisuke; Yasuda, Ichiro; Komatsu, Naohiro; Miyaaki, Hisamitsu; Ohnita, Ken; Yamao, Takuji; Oba, Kazuo; Ichikawa, Tatsuki; Nakao, Kazuhiko
Abstract: Background/Purpose: Recurrence of ampullary neoplasms after endoscopic papillectomy (EP) has not been well elucidated. This study aimed to clarify the predictive factors for recurrences after EP. We also aimed to investigate the retreatment of the recurrent lesions and their outcomes. Methods: This multicenter, retrospective cohort study included 96 patients with ampullary neoplasms who underwent EP at four tertiary centers between January 2000 and October 2018. Results: The pathological diagnoses of resected specimens confirmed adenoma in 62 and adenocarcinoma in 34 patients (six Tis, 24 T1a, three T1b, one inconclusive). Complete resection was confirmed for 79 patients (82.3%). Recurrent lesions were observed in 13 patients (13.5%) during a median follow‐up of 3 months (1‐36 months) after EP. The predictive factors of recurrence were piecemeal resection, and non‐negative horizontal or vertical margin in univariate analysis. Non‐negative vertical margin was the only independent predictive factor of recurrence in the multivariate analysis. The recurrent lesions were treated endoscopically in 11 patients. Recurrence after the endoscopic retreatments was observed in one patient. Conclusions: Complete resection with negative vertical margin is an important factor in preventing the recurrence of ampullary neoplasms after EP. Endoscopic retreatments are also feasible for recurrent lesions. Abstract : Highlight Takahashi and colleagues analyzed endoscopic papillectomy data from 96 patients. The complete resection and recurrence rates were 82.3% and 13.5%, respectively. A non‐negative vertical margin was an independent predictive factor of recurrence. Complete resection and a negative vertical margin are important factors in preventing the recurrence of ampullary neoplasms after endoscopic papillectomy.